Editorial to Child and Adolescence Psychopharmacology - Juckel, G. (Pharmacopsychiatry, 2016)
The editors of Pharmacopsychiatry have decided in 2016 to prepare special issues regularly in order provide our readers volumes of the journal with a thematic focus 1. The first such special issue is dedicated to the field of child and adolescent psychopharmacology. Many young patients are treated with psychotherapeutic, but also pharmacotherapeutic, methods worldwide. Most of our psychopharmacological agents are not approved by the federal institutions for persons under 18 years old. However, severe mental illnesses like schizophrenia, depression, anxiety, ADHD, and bipolar disorder frequently require pharmacological treatments in children and adolescents. We also see a wide range of rather unspecific emotional and behavioral disturbances up to excitation crises or suicidal acts in this young population, so that we see the necessity for standardized and valid psychopharmacological treatment regimens based on meta-analyses, randomized controlled trials, and guidelines 2. Child and adolescent psychiatry is unfortunately far away from this; industry-supported research is rare in this area, but also not all child and adolescent psychiatrists see the importance of psychopharmacological treatment and trust specific psychotherapy, psychoeducation, and educational strategies. These are all extremely important treatments, but one can/should think that psychopharmacotherapy is an important addition and often a cornerstone for the other treatments.